EARLY DETECTION OF PARKINSON'S DISEASE EDUCATION AND FREE HEALTH CHECK-UPS FOR RESIDENTS IN LAMONGAN REGENCY - Maghfiroh, Isni Lailatul; Ningrum, Dhiajeng Widya; Shinta, Gia Ayu; Diana, Fara Nur (Journal of Community Research and Engagement, 2024)
Parkinson's disease is the second most common neurodegenerative disease in the world after Alzheimer's disease. The global prevalence of Parkinson's disease is approximately 300 cases per 100,000 people per year, increasing by more than 3% in those over 80 years old. In Indonesia, most cases of Parkinson's disease are found in individuals aged 40-70 years, with an average age of 58-62 years, and only about 5% occur in those under 40 years old. The health education on Parkinson's disease was conducted using lectures, discussions, and question-and-answer sessions. This activity took place in Deket Wetan Village, Deket Sub-district, Lamongan Regency, on Saturday, February 11, 2023, from 6:30 to 7:30 PM WIB and was attended by approximately 13 members of the PKK (Family Welfare Program). The event ran smoothly, and all participants were very enthusiastic about the activity.